Surely when you subtract the two final equations (which by the way is NOT the substitution method), the x terms are eliminated leaving z = -3...
Hello, I have the following set of three linear equations. I am trying to solve for x,y,z using substitution.
x - y - z = 0
-2x + 4y = 0
3y - 2z = 3
My first step is to isolate 'y=z-x'
I then substitute y into the next two equations resulting in:
-3x + 2z = 0
-3x + z = 3
Now when I subtract these I get z = -3, however the answer should be z = 3.
What am I doing wrong here ?
Thanks kindly for any help.